2011
DOI: 10.1097/00054725-201112002-00040
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Intervention to Improve Medication Adherence in Nonadherent Inflammatory Bowel Disease Patients

Abstract: Background: Medication nonadherence in inflammatory bowel disease (IBD) can lead to suboptimal control of the disease, decreased quality of life, and poorer outcomes. This pilot study evaluated the feasibility, intervention mechanism, and potential effectiveness of a threemonth continuous self-improvement (CSI) intervention to enhance medication adherence in adult nonadherent IBD patients. Methods: Adult IBD patients taking a daily or twice-daily dosed maintenance medication were screened for two months to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This personal system change was key to improving eating behaviors. In another example, two studies [25,38] used the MEMS report which delineates colored dots for each day and time the MEMS is opened and a medication is presumed administered.…”
Section: Methods Guiding Personal Improvementmentioning
confidence: 99%
See 4 more Smart Citations
“…This personal system change was key to improving eating behaviors. In another example, two studies [25,38] used the MEMS report which delineates colored dots for each day and time the MEMS is opened and a medication is presumed administered.…”
Section: Methods Guiding Personal Improvementmentioning
confidence: 99%
“…Six studies focused on healthy adults attempting to enhance personal lifestyle improvement such as studying, eating, exercise, work habits, and stress [2,3,4,21,23,44] . In the remaining three studies focusing on chronically ill adults, CSI was utilized to augment kidney transplantation immunosuppression medication adherence [38] , to decrease cardiac risk factors through weight loss [29] , and enhance medication adherence in people with inflammatory bowel disease [25] . Data from included studies are reported in Table 1 (CSI Systematic Review of Included Studies).…”
Section: Descriptions Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations